2017 IFIP/IEEE Symposium on Integrated Network and Service Management (IM) 2017
DOI: 10.23919/inm.2017.7987442
|View full text |Cite
|
Sign up to set email alerts
|

Q-Learning for Policy Based SON Management in wireless Access Networks

Abstract: Abstract-Self organized networks has been one of the first concrete implementations of autonomic network management concept. Currently, several Self-Organizing-Network (SON) functions are developed by Radio Access Network (RAN) vendors and already deployed in many networks all around the world. These functions have been designed independently to replace different operational tasks. The concern of making these functions work together in a coherent manner has been studied later in particular in SEMAFOUR project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In [9] the authors showed that a centralized RL algorithm (Q-learning) is able to learn the optimal policy, satisfying the operator's objectives. However, when the network size, the number of SON functions and instances, as well as the number of possible SCV sets for each SON function grow, the action space that has to be explored by the RL agent explodes, leading to a very slow convergence.…”
Section: Fig 2: C-pbsmmentioning
confidence: 99%
“…In [9] the authors showed that a centralized RL algorithm (Q-learning) is able to learn the optimal policy, satisfying the operator's objectives. However, when the network size, the number of SON functions and instances, as well as the number of possible SCV sets for each SON function grow, the action space that has to be explored by the RL agent explodes, leading to a very slow convergence.…”
Section: Fig 2: C-pbsmmentioning
confidence: 99%